Le développement du bar homosexuel comme institution [1967] - Nancy Achilles (Genre, Sexualité et Société)
This article is devoted to the gay bar scene in San Francisco in the 1960s. The author emphasizes police persecution and the structuring role of perpetual law enforcement interventions on community cohesion, sense of belonging, and the emergence of collective identity as an oppressed group. She shows that advances in rights were brought about by bar owners and that the struggle to maintain commercial establishments was constituted as a political issue, their existence being considered a collective right (that of assembly) under constant threat.